2014
DOI: 10.1111/ijcp.12394
|View full text |Cite
|
Sign up to set email alerts
|

The effect of L-thyroxine substitution on lipid profile, glucose homeostasis, inflammation and coagulation in patients with subclinical hypothyroidism

Abstract: Except for a reduction in systolic and diastolic BP, thyroid substitution therapy does not affect lipidaemic profile, systematic inflammation, glucose homoeostasis or coagulation in patients with SH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
1
11
1
3
Order By: Relevance
“…Numerous studies have estimated the effect of L-thyroxine replacement treatment on serum lipid levels in patients with sub-clinical hypothyroidism; however, their results were inconsistent. In a recent study by Anagnostis et al (22), L-thyroxine replacement treatment exerted no effect on serum lipid levels of patients with mild sub-clinical hypothyroidism, whose TSH levels were <7 mIU/l. However, Tagami et al (2) reported a significant decrease of TC and LDL-C following L-thyroxine replacement therapy.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Numerous studies have estimated the effect of L-thyroxine replacement treatment on serum lipid levels in patients with sub-clinical hypothyroidism; however, their results were inconsistent. In a recent study by Anagnostis et al (22), L-thyroxine replacement treatment exerted no effect on serum lipid levels of patients with mild sub-clinical hypothyroidism, whose TSH levels were <7 mIU/l. However, Tagami et al (2) reported a significant decrease of TC and LDL-C following L-thyroxine replacement therapy.…”
Section: Discussionmentioning
confidence: 88%
“…Patients with sub-clinical hypothyroidism, particularly those with positive thyroid antibodies, are at risk of developing overt hypothyroidism at an estimated rate of 2.0-4.3% per year (3,22). L-thyroxine replacement treatment is currently the major therapy for sub-clinical hypothyroidism, which is administered with the following purposes: First, in order to prevent progression to overt hypothyroidism and second, to reduce symptoms of thyroid hormone deficiency (23).…”
Section: Discussionmentioning
confidence: 99%
“…32 Tra i farmaci che possono favorire lo sviluppo della HT e/o la sua progressione verso l'ipotiroidismo vi sono l'interferone alfa, 33 l'interleuchina-2efattori stimolanti di colonie di granulociti e macrofagi (GM-CSF), 34,35 farmaci antiretrovirali, 36 anticorpi monoclonali, 7,8 litio e amiodarone. 37 Una estensiva review su questo argomento è stata recentemente pubblicata. 38 Per quanto riguarda il possibile ruolo di infezioni virali, sono stati riscontrati componenti di virus quali Parvovirus B19, Coxachie ed Herpes, 39,40 HCV 41 in tiroidi di HT ma vi sono risultati contrastanti e poco convincenti, per la difficoltà di definire un'associazione causale certa.…”
Section: Fattori Geneticiunclassified
“…Inoltre, l'IpoS può peggiorare il compenso glicometabolico nei soggetti con DMT2, ed il trattamento con L-T4 può ridurre l'insulino-resistenza e migliorare il compenso glicometabolico. 1,37 Di diversa natura è ben nota la relazione tra IpoS e diabete mellito tipo 1 (DMT1), certamente determinata dalla comune eziopatogenesi autoimmune, a causa della quale circa il 30% dei soggetti con DMT1 può presentare un IpoS. 1 Numerosi studi osservazionali hanno evidenziato un'importante correlazione tra IpoS ed incremento della concentrazione sierica del colesterolo totale, del colesterolo LDL, dei trigliceridi; tale correlazione è stata confermata da almeno una metanalisi.…”
Section: Significato Biologico Dell'ipotiroidismo Subclinico Nell'adultounclassified
“…In a recent prospective study, we did not find any significant effect of L-thyroxine replacement therapy on lipid profile, coagulation markers, systemic inflammation and glucose homoeostasis in SCH patients (mean baseline TSH: 6.8 mIU/L). It only reduced blood pressure, especially in those with TSH >7 mIU/L [5]. The duration of L-thyroxine therapy, DM and nephropathy and the multi-factorial origin of the latter may also play a critical role in the effect of L-thyroxine on renal function.…”
mentioning
confidence: 99%